Characterization of fruit development and potential health benefits of arrayan (Luma apiculata), a native berry of South America. (1st April 2016) - Fuentes, Lida; Valdenegro, Mónika; Gómez, María-Graciela; Ayala-Raso, Aníbal; Quiroga, Evelyn; Martínez, Juan-Pablo; Vinet, Raúl; Caballero, Eduardo; Figueroa, Carlos R.
Highlights: Arrayan fruit is a very rich source of antioxidant compounds. Arrayan extracts help in the prevention of vascular damage induced by high glucose. Arrayan fruit have a promising food and healthy potential. Abstract: The arrayan berry ( Luma apiculata ) is a native fruit from South America that belongs to the Myrtaceae family. To elucidate and characterize the developmental process and the potential health benefits of this edible fruit, quality and physiological parameters, along with antioxidant capacity, were evaluated during four clearly defined developmental stages of the fruit in two seasons. Fruit firmness slowly decreases during fruit development, whereas the solid soluble content/titratable acidity ratio (SSC/TA) increases significantly in the final stages of development. The measurement of low respiration rates and low ethylene production during growth and ripening suggested that the arrayan berry should be classified as a non-climacteric fruit. Arrayan berries show a significant increase in their antioxidant capacity from small green to black ripe fruit. FRAP and TEAC assays showed high correlations with total polyphenolic content (TPC) during ripening and high antioxidant capacity at all fruit stages, showing greater values in ripe fruit (FRAP: 24 ± 2 and 28 ± 3 μM FeSO4 /gFW; TEAC: 18 ± 2 and 20 ± 1 Eq. Trolox/gFW for each season, respectively) than those observed in the blueberry (FRAP: 10 ± 2 and 19 ± 3 μM FeSO4 /gFW; TEAC: 10 ± 2 and 17 ± 3). In addition, bioactive assays using ripe fruit extracts show presence of flavonol and anthocyanins, a high ORAC value (62, 500 ± 7000 μmol/gDW) and a concentration-dependent vascular protection under high glucose conditions. The results obtained show that these endemic berry fruits have a promising potential as functional food.